2005
DOI: 10.1097/01.aog.0000171109.53832.8d
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Compared With Intermittent Epidural Infusion on Progress of Labor and Patient Satisfaction

Abstract: This study provides evidence that both continuous and intermittent epidural infusion produce comparable analgesia achieving equivalent maternal satisfaction with no difference regarding the duration of labor between them. Although patients receiving epidural analgesia experienced longer labors compared with controls, both mothers and neonates were unharmed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
1
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 19 publications
1
17
1
3
Order By: Relevance
“…Most studies also showed that local anaesthetic consumption is reduced with ITU (133,134,136,137). Despite less anaesthetic consumption, obstetric outcome is usually similar between the two modalities (135)(136)(137)(138)(139)(140), except for more spontaneous deliveries with ITU in the study by Smedstad et al (134). So basically, CEI and ITU are quite similar in terms of quality of analgesia and incidence of side-effects with a tendency towards better performance for the ITU technique.…”
Section: Intermittent Top-ups Versus Continuous Infusionmentioning
confidence: 97%
See 2 more Smart Citations
“…Most studies also showed that local anaesthetic consumption is reduced with ITU (133,134,136,137). Despite less anaesthetic consumption, obstetric outcome is usually similar between the two modalities (135)(136)(137)(138)(139)(140), except for more spontaneous deliveries with ITU in the study by Smedstad et al (134). So basically, CEI and ITU are quite similar in terms of quality of analgesia and incidence of side-effects with a tendency towards better performance for the ITU technique.…”
Section: Intermittent Top-ups Versus Continuous Infusionmentioning
confidence: 97%
“…However many studies reported no differences in terms of analgesic quality between ITU and CEI (133)(134)(135), and some reported that ITU was associated with better analgesia (136)(137). Most studies also showed that local anaesthetic consumption is reduced with ITU (133,134,136,137). Despite less anaesthetic consumption, obstetric outcome is usually similar between the two modalities (135)(136)(137)(138)(139)(140), except for more spontaneous deliveries with ITU in the study by Smedstad et al (134).…”
Section: Intermittent Top-ups Versus Continuous Infusionmentioning
confidence: 98%
See 1 more Smart Citation
“…У aCOg препорукама из 2002. године наводи се да треба сачекати цервикалну дилатацију од бар четири-пет центиметара да би се избегла повећана инциденција царских резова (4). Ипак, још је Chestnut 1994. године (5), а последњих година и други аутори, lieberman, eltzsing, Camman (6)(7)(8), кренуо с извођењем епидуралне аналгезије при дилатацији цервикса од три и по центиметра, односно два центиметра, при чему није порастао број оперативних и инструменталних довршења порођаја, а породиље су, разумљиво, биле задовољније анестезијом. Циљ овог рада био је да се одговори на питање да ли има оправдања за аналгезију у порођају и потребе за њом, као и да се прикажу основни принцип и техника извођења епидуралне аналгезије, специфичности код породиља, ефекти на мајку и плод и дилеме које прате ту методу.…”
Section: уводunclassified
“…(See Table 3) As shown by Bussche et al [Bussche EV et al, 2007], the main factor that determined the parturients' decision was social influence. There are studies which report numerous factors that influence the decision to use epidural analgesia, such as age, level of education and www.intechopen.com health insurance status [Atherton MJ et al, 2004;Obst TE et al, 2001;Rust G et al, 2004;Salim R et al, 2005]. A low percentage of epidural analgesia procedures during labour is noticed (25,36%), with a majority of 61,53% among patients that graduated from higher education.…”
Section: The Situation Of Epidural Analgesia In Childbirth In Romaniamentioning
confidence: 99%